1999
DOI: 10.1289/ehp.99107761
|View full text |Cite
|
Sign up to set email alerts
|

Examining associations between childhood asthma and traffic flow using a geographic information system.

Abstract: Using geographic information systems (GIS) and routinely collected data, we explored whether childhood residence near busy roads was associated with asthma in a low-income population in San Diego County, California. We examined the locations of residences of 5,996 children [less than/equal to] 14 years of age who were diagnosed with asthma in 1993 and compared them to a random control series of nonrespiratory diagnoses (n = 2,284). Locations of the children's residences were linked to traffic count data at str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(164 citation statements)
references
References 23 publications
7
155
0
2
Order By: Relevance
“…There was some evidence that infants and girls were at highest risk. These results are consistent with those of a cross-sectional study 26 and 2 case-control studies 27,28 showing increased risk of asthma hospitalizations or other medical care visits with increasing home traffic density indices. These results are also consistent with those of a longitudinal analysis of recurrent respiratory hospital encounters using traffic indices, 20 but associations in that study were not significant for patients with a primary diagnosis of asthma.…”
Section: Overview Of Findings and Implicationssupporting
confidence: 91%
“…There was some evidence that infants and girls were at highest risk. These results are consistent with those of a cross-sectional study 26 and 2 case-control studies 27,28 showing increased risk of asthma hospitalizations or other medical care visits with increasing home traffic density indices. These results are also consistent with those of a longitudinal analysis of recurrent respiratory hospital encounters using traffic indices, 20 but associations in that study were not significant for patients with a primary diagnosis of asthma.…”
Section: Overview Of Findings and Implicationssupporting
confidence: 91%
“…One found that trafficrelated pollution is associated with respiratory symptoms in children (Kim et al, 2004). The other found no increase in asthma prevalence related to residence proximity to high traffic roads in a cohort of low income children, although they reported an increase in medical visits for asthma by traffic-exposed children (English et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
“…For studies in the US, it has been reported that automated address matching was poor for rural areas (match rate of 20 -30% ) and much higher (98% ) for the largest urbanized county in North Carolina (Vine et al, 1997 ). A study in San Diego County reported a 85% address match, with missing data due in part to listing of PO boxes and incomplete addresses (English et al, 1999 ) .…”
Section: Application Of Gismentioning
confidence: 99%
“…In a study in San Diego, traffic flow in buffers of 550 ft was used to characterized local scale exposures (English et al, 1999) .…”
Section: Local Scalementioning
confidence: 99%